2022
DOI: 10.3389/fpubh.2022.814596
|View full text |Cite
|
Sign up to set email alerts
|

The Black Panther, Masculinity Barriers to Medical Care, and Colorectal Cancer Screening Intention Among Unscreened American Indian/Alaska Native, Black, and White Men

Abstract: ObjectiveTo determine if masculinity barriers to medical care and the death from colorectal cancer (CRC) of actor Chadwick Boseman (The Black Panther) influenced CRC early-detection screening intent among unscreened American Indian/Alaska Native (AIAN) and Non-Hispanic-Black (Black) men compared with Non-Hispanic-White (White) men.MethodsUsing a consumer-panel, we surveyed U.S. men aged 18–75 years (N = 895) using the 24-item Masculinity Barriers to Medical Care (MBMC) scale. We calculated the median score to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Similarly, a 2013 study with American Indians under age 50 found that Native men did not like to talk about CRC, partly because of a “homophobe type thing” and partly because they might be viewed as “a softy” [ 40 ]. Finally, a study that focused on the role of “masculinity barriers” to medical care in racially diverse populations found that American Indian/Alaska Native men were least likely to report CRC screening intent (51.1%) compared with African American (68%) and White men (64%) ( p < 0.001); moreover, Native men who exhibited more masculinity-related barriers to care were less likely to have CRC screening intent compared to other racial groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 2013 study with American Indians under age 50 found that Native men did not like to talk about CRC, partly because of a “homophobe type thing” and partly because they might be viewed as “a softy” [ 40 ]. Finally, a study that focused on the role of “masculinity barriers” to medical care in racially diverse populations found that American Indian/Alaska Native men were least likely to report CRC screening intent (51.1%) compared with African American (68%) and White men (64%) ( p < 0.001); moreover, Native men who exhibited more masculinity-related barriers to care were less likely to have CRC screening intent compared to other racial groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reinforcing this idea, a study by Heslin et al discovered that men who self-identify as gay or bisexual exhibited a 67% higher likelihood of completing colonoscopies than those identifying as heterosexual [ 35 ]. The findings further bring to light the intricate interplay between the norms associated with masculine roles, the decision to undergo invasive screening procedures, and apprehensions about being labeled as gay [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…Traditional gender roles are highly ingrained in many African American communities. Men are frequently portrayed as strong, stoic defenders, whereas women are portrayed as caregivers [ 36 ]. While these roles are evolving, they can affect health perceptions and behaviors, including decisions on preventative healthcare such as colonoscopies.…”
Section: Reviewmentioning
confidence: 99%
“…Lower screening rates and higher CRC rates are attributed to many factors, including masculinity barriers and medical mistrust [ 8 ]. Indigenous masculinity barriers are closely correlated with decreased CRC screening intentions [ 9 ]. Other screening barriers include language, discrimination, cultural insensitivity, fear, discomfort, and screening preparation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%